Taxation of the Public Sector in Germany – An Introduction - Lang, Fritz (University of Wroclaw. Faculty of Law, Administration & Economics, 2017)
The public sector in Germany is subject to both income tax and value-added tax when its activities go beyond the area of public administration to the extent that they enter into competition with other providers. The taxation of public-sector entities is intended primarily to prevent the distortion of competition. The delimitation of the spheres that are relevant for taxation purposes requires a complex system of statutory provisions. The German Tax Amendment Act 2015 seeks to establish a new statutory basis for the VAT treatment of the public sector that is compliant with EU law.
Keywords: taxation; public sector; Germany